2019
DOI: 10.29326/2304-196x-2019-3-30-3-8
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus: Use of Genetic Markers in Analysis of Its Routes of Spread

Abstract: At present no effective measures for specific prevention and treatment of African swine fever have been developed. The control strategy for the disease is designed for rapid diagnosis of infected animals with subsequent slaughter and decontamination (stamping out). The present review deals with current epidemic situation for African swine fever and examines features of the virus genomics and genetic differentiation of the isolates. The Russian Federation has been ASF-infected since 2007. Since that time the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…There are two types according to the insertion: MGF-1 type without insertion and MGF-2 type with a new long insertion of 17 nucleotides (GATAGTAGTTCAGTTAA). MGF-2 type has been observed in seven Russian isolates from Vladmir and Tver regions, and in nine Polish isolates [20]. For the analysis of Korean isolates, we used a set of primers that amplified a~500 bp fragment located in the IGR of MGF 505 9R/10R.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two types according to the insertion: MGF-1 type without insertion and MGF-2 type with a new long insertion of 17 nucleotides (GATAGTAGTTCAGTTAA). MGF-2 type has been observed in seven Russian isolates from Vladmir and Tver regions, and in nine Polish isolates [20]. For the analysis of Korean isolates, we used a set of primers that amplified a~500 bp fragment located in the IGR of MGF 505 9R/10R.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that all Korean isolates have the characteristics of MGF-1 without insertion in this region, and the sequence of IGR of MGF 505 9R/10R was 100% identical to that of Pol16 20186 o7, Belgium 2018/1, Pig/HLJ/2018, DB/LN/2018, and China/2018/AnhuiXCGQ (Figure 4, Table 2). Recently, the MGF-3 type, which contains two identical insertions in MGF 505 9R/10R, was found in the Tver region of Russia (Tver1112/Zavi) [20]. Since the first outbreak of ASF in South Korea, we isolated 14 ASF viruses from infected domestic pig farms and all the isolates showed the ability of HAD.…”
Section: Resultsmentioning
confidence: 99%
“…On 24 January 2014, two cases of ASF in wild boars were found in Lithuania and later in wild boars in Latvia, Estonia, and part of Poland bordering on Belarus (Gallardo et al, 2014;Pejsak et al, 2014a;Pejsak et al, 2014b). ASF spread further in Moldova, the Czech Republic, and Romania in 2017, in Hungary, China, Belgium, and Mongolia in 2018, and further to South East Asia (Mazloum et al, 2019). Since no vaccine is available against ASF, the only way to control and eradicate the disease and the spread of the virus is based on classical disease control methods, such as surveillance, rapid detection and identification of ASF virus-specific antigens or DNA and antibodies, and stamping out of infected animals ( (Haines et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…торый участвует в сборке капсида, а также генов E183L и CP204L, кодирующих соответственно структурные белки vp54 и vp30 (5,6).…”
unclassified